AN ANALYSIS OF NAPOLEON’S CHARACTER USING PSYCHOLOGICAL APPROACH AS SEEN ON GEORGE ORWELL’S ANIMAL FARM - Mrdinata, Alfajri; Asridayani, Asridayani; Oktariza, Dodi (Krinok:Jurnal Linguistik Budaya, 2023)
This study is the result of a study which consists of the researcher’s description about the Napoleon’s character that as a round (complex) character as depicted in the novel Animal Farm written by George Orwell. In this study, the researcher uses Descriptive research involves collecting data in order to unscrew question concerning current status of subject the research is once the way to collect the data on our subject. Thus, this study is simply an appreciation of the novel which is presented in the descriptive form which is qualitative in nature. The main analysis consists of several points: The aggressive shrew character that becomes early leader of Animal Farm. After he successfully eliminates “Snowball” that is becomes his rival, he gradually increases his personal power and privileges, while simultaneously tightening the control over the other characters in Animal Farm. By seizing onto a populist revolution and turning it into his personal regime. Napoleon itself is a board as a symbol of crafty character that reflect on Russian regime, and also another characterization of human characteristic and animal characteristic.